2003
DOI: 10.1021/jm0302445
|View full text |Cite
|
Sign up to set email alerts
|

Novel sst4-Selective Somatostatin (SRIF) Agonists. 2. Analogues with β-Methyl-3-(2-naphthyl)alanine Substitutions at Position 8

Abstract: We present a family of human sst(4)-selective, high-affinity (IC(50) = 2-4 nM) cyclic somatostatin (SRIF) octapeptides. These peptides result from the substitution of dTrp(8) in H-c[Cys(3)-Phe(6)-Phe(7)-DTrp(8)-Lys(9)-Thr(10)-Phe(11)-Cys(14)]-OH (SRIF numbering) (ODT-8) by one of the four conformationally biased stereoisomers of beta-methyl-3-(2-naphthyl)alanine (beta-Me2Nal). Whereas H-c[Cys-Phe-Phe-DNal-Lys-Thr-Phe-Cys]-OH (ODN-8, 2) has high affinity and marginal selectivity for human sst(3) (Reubi et al., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(65 citation statements)
references
References 78 publications
1
64
0
Order By: Relevance
“…For example, the position and the number of aromatic rings involved in binding are different for the two ligands, suggesting that these hydrophobic residues interact with different regions of the sst 1 and sst 4 receptors, respectively ( Figure 3D and 3E). On the other hand, most of the previously published analogues binding with high affinity to sst 2 receptor were also binding to sst 5 receptors with nM affinity and sometimes to sst 3 receptors as well. Melacini et al, proposed a pharmacophore model for these analogues binding nonselectively to all of the three receptors ( Figure 3C).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, the position and the number of aromatic rings involved in binding are different for the two ligands, suggesting that these hydrophobic residues interact with different regions of the sst 1 and sst 4 receptors, respectively ( Figure 3D and 3E). On the other hand, most of the previously published analogues binding with high affinity to sst 2 receptor were also binding to sst 5 receptors with nM affinity and sometimes to sst 3 receptors as well. Melacini et al, proposed a pharmacophore model for these analogues binding nonselectively to all of the three receptors ( Figure 3C).…”
Section: Discussionmentioning
confidence: 97%
“…Hence, it can be concluded that this aromatic ring is not crucial for sst 2 binding, and is crucial for sst 3 and sst 5 binding, as the binding to receptors 3 and 5 decreased ( Table 1). Replacement of Phe at position 7 by an amino acid having a longer side chain, such as Aph has also decreased the binding to sst 3 and sst 5 receptors, retaining high binding affinity to sst 2 receptors. Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same is true for the cyclohexapeptide TT-232 (264). Because some tumors express sst 1 and/or sst 4 but lack sst 2 and sst 5 , efforts have been put into the development of sst 1 and sst 4 subtype-specific analogues (167,168). More recently, high-affinity subtype-selective nonpeptide agonists of sst 1 -sst 5 were identified in combinatorial libraries, based on molecular modeling of known peptide agonists (459); these structure are, however, less suitable as carriers for targeting sst receptors with radioisotopes.…”
Section: Reprintsmentioning
confidence: 98%
“…Recently amino acid analysis by CE have been reviewed by Rizzi [22] and Chankvetadze [23], but very few papers dealing with capillary electrophoresis (CE) of ␤-methyl-amino acids have appeared. Gübitz and coworkers [17] applied ligand-exchange CE,Érchegyi et al [24] separated erythro and threo stereoisomers of ␤-methyl-3-(2-naphthylalanine) by CE and very recently Jiang et al [25] resolved some racemic erythroand threo-␤-methyl-amino acid enantiomers. Survey of literature data revealed that the baseline separation of all four stereoisomers in one run is rarely attainable.…”
Section: Introductionmentioning
confidence: 99%